Electrospun nanofibers of ɛ-polycaprolactone (PCL) and natural products for dental applications - Alexandrino, Luís Pedro Vieira (2023)
Periodontal disease, or periodontitis, is a problem that many people suffer from, and no treatment can eliminate without any doubt the issue. Periodontal disease causes the breakdown of periodontal structure, leading to a search on creating structures capable of facilitating periodontal tissue regeneration. In this master's thesis, the approach to overcome the problem was to manufacture fibrous membranes through the electrospinning technique to mimic the extracellular matrix. Electrospun membranes of poly(caprolactone) (PCL) and PCL loaded with natural products such as aloe vera (AV) and curcumin (CUR), were produced, to provide an antibacterial effect, using benign solvents, as acetic and formic acids. Electrospun membranes of PCL, PCL/AV and PCL/CUR were successfully produced, with a diameter range of fibers of 120-180 nm, having been observed in some of them, the formation of nano-nets between the fibers, reaching diameters of 25-45 nm. The fibers were analyzed using Scanning Electron Microscope (SEM). The loading of aloe vera and curcumin in the fibers was confirmed using Attenuated Total Reflectance – Fourier Transform Infrared (ATR-FTIR). Wettability tests and antibacterial assay (E. coli and S. Aureus) were performed in every produced membrane. The study demonstrated that aloe vera and curcumin can be successfully loaded into a PCL membrane without changing the wettability of the membrane. The diffusion disks method, that quantifies the diameter of inhibition halo, it was not detected any antibacterial activity with the loading of aloe vera and curcumin. Overall, PCL membranes loaded with the different content percentages of aloe vera and curcumin were produced successfully, with nanostructure mimicking the extracellular matrices found in the periodontal structure. From a morphological perspective, these membranes are promising scaffolds for tissue engineering. The possibility of controlling the production of nano-net and a more systematic study of these membranes' antibacterial activity thus appears as aspects of great interest for the continuation of the work developed.